Acute heart failure in women: phenotypes and outcomes in Mexico. Gender differences?. (14th October 2021) - Alvarez-San Gabriel, A; Gonzalez-Pacheco, H; Arias-Mendoza, A; Guizar-Sanchez, C; Manzur-Sandoval, D; Araiza-Garaygordobil, D; Jordan-Rios, A; Gopar-Nieto, R; Sierra-Lara Martinez, D; Mendez-Ortiz, A; Briseno-De La Cruz, J L; Favela-Garcia, K; et al.
Abstract: Background: Latin America has limited information about sex differences in acute heart failure and about hospital outcome. This study sought to examine clinical features and outcomes of patients with AHF in a coronary care unit of a single Mexican institution. Aims: To examine the sex differences in clinical features, phenotype, etiologies and mortality of patients with acute heart failure in a single institution of Latin-America. Methods: This was a retrospective study of consecutive patients hospitalized with AHF in a coronary care unit of a Mexican teaching hospital between January 2006 and December 2020. Results: During the study period, 24, 262 patients were hospitalized, 9, 408 (38.8%) had AHF, of which 3, 230 (34.3%) were women. Women with AHF, compared to men with AHF, were older (median, 64 vs. 61 years, P<0.0001) and more likely to have a history of hypertension, stroke, atrial fibrillation, and hypothyroidism. The ischemic heart disease was more frequent in men (67.8% vs 40.5%; p<0.0001), however, valvular heart disease and cardiomyopathies were more frequent in women (32.9% vs 16.9% and 16.0 vs 10.2%, respectively; p<0.0001) (figure 1). At presentation, women had a higher frequency of worsening chronic HF (59.8%), worse NYHA class, preserved left ventricular ejection fraction (LVEF) (median, 45% vs 38%; P<0.0001), and lower estimated glomerular filtration rates. Overall, unadjusted in-hospital mortality was higher in women (18.9 vs 16.1, p<0.0001), but only different in ischemic heart disease (18.2 vs 15.7, p<0.03) and valvular heart disease (21.8 vs 18.2%, p<0.03). In-hospital mortality adjusted for age and LVEF showed that women had a higher risk of death. (Odds ratio 1.34; 95% CI, 1.19–1.51, P<0.0001) (figure 2). Conclusions: In this cohort of Mexican patients hospitalized with AHF, there were important differences in clinical characteristics and aetiologies between women and men. Women have a higher frequency of worsening chronic HF and as well as renal function. Nevertheless, despite having a preserved LVEF, in-hospital mortality was higher in women compared to men. Funding Acknowledgement: Type of funding sources: None.